TorakochirurgiaApplication of TachoComb resorbable fibrinogen-collagen patch to seal up the lung parenchyma reduces chest tube duration after thoracic surgery - Kowalewski, Janusz; Dancewicz, Maciej; Bella, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: There are several approaches to achieve air-tightness of the lung after surgery: manual suturing, staplers, tissue sealing or using the TachoComb fibrinogen-collagen patch. The aim of the study was to evaluate the influence of TachoComb application to seal up the lung on chest tube duration after thoracic surgery. Materials and methods: The following operations were performed in 122 analyzed patients between 2003 and 2005: bullectomy for pulmonary emphysema, decortication, partial pulmonary resection with coexisting diffuse pleural adhesions. In 58 patients the surface of the lung was sutured manually or by staplers, but in 64 cases patches of TachoComb were used additionally. Results: Comparison of the two arms revealed significantly shorter air leakage time and lower cumulative chest drain volumes in the TachoComb subgroups of patients after decortication and operated on with coexisting diffuse pleural adhesions. Conclusions: The application of TachoComb significantly reduces chest tube duration after selected thoracic operations.